2019
DOI: 10.1177/1087054719859081
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in the Management of ADHD: Literature Review of Telemedicine in ADHD

Abstract: Objective: Telemedicine has been used successfully in several medical specialties with favorable patient outcomes, satisfaction, in a cost-effective manner. However, its use in the context of ADHD remains unclear. Our main aim was to investigate what is known about the use of telemedicine in ADHD. Method: We conducted a systematic search of the literature assessing telemedicine in ADHD in PubMed, PsycINFO, and Medline. Included were original articles published in English with the main aim to assess the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 34 publications
0
39
0
4
Order By: Relevance
“…Prior to the COVID‐19 pandemic, the healthcare industry was leveraging technology to address health access disparities (Rutledge et al, 2014; Spencer et al, 2020; Ward et al, 2015) and telehealth services are likely to become more widely integrated into our healthcare system (Lee et al, 2020). Telehealth affords the ability to bring specialty care knowledge to rural or medically underserved areas (Lindgren et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the COVID‐19 pandemic, the healthcare industry was leveraging technology to address health access disparities (Rutledge et al, 2014; Spencer et al, 2020; Ward et al, 2015) and telehealth services are likely to become more widely integrated into our healthcare system (Lee et al, 2020). Telehealth affords the ability to bring specialty care knowledge to rural or medically underserved areas (Lindgren et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Telepsychiatry can be an effective way to deliver care for ADHD [ 70 74 ]. A review has concluded that telemedicine was cost-effective for children and suggested that research should also be conducted in adults with ADHD [ 75 ]. In the pipeline, there is a randomized controlled trial underway to investigate the efficacy of a web-assisted self-help programme for parents of children with ADHD [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…The focus on adult patients with ADHD is another strength of the study, as research on the suitability of telepsychiatric treatment for adult patients with ADHD is particularly scarce [51] and the various symptoms of ADHD, such as inattentiveness and organisational deficits, have distinct potential to interfere with this type of treatment modality. Due to ADHD’s high prevalence in adults, often demanding continuous treatment, and its frequent presentation with severe psychiatric co-morbidities, patients with ADHD are a particularly important group to study.…”
Section: Discussionmentioning
confidence: 99%
“…In their recent review of the literature, Spencer and colleagues [51] identified 11 relevant primary studies with sample sizes of at least 20 participants investigating the use of telemedicine in patients with ADHD. Overall, the results were promising; telepsychiatry was both well accepted and valued by patients and also associated with improved outcomes.…”
Section: Telepsychiatry For Adults With Adhdmentioning
confidence: 99%